Pengaruh Kandungan Informasi komponen Laporan Arus Kas, Laba Akuntansi Dan Size Perusahaan Terhadap Return Saham Pada Perusahaan Consumer Good di Bursa Efek Indonesia - laila zulviana (Universitas Tanjungpura, 2020)
This study aims to examine the impact of the information content component of the cash flow statements, accounting profit, and company sizes on stock returns in consumer goods companies listed on the Indonesia Stock Exchange in the 2014-2017 period. The population in this study are corporations listed on the Indonesia Stock Exchange, specifically consumer goods companies. The sample were obtain by purposive sampling method. There are 30 companies that match the criteria. The data analysis was contucted using SPSS version 22. The technique of data analysis was descriptive statistics, classic assumption tests, hypothesis testing utilising multiple linear regression analysis. The research findings explicated several discoveries such as the following : 1) Operating cah flow has a negative and no significant effect on stock return, 2) Investment cash flow holds a positive and not significant effect on stock return, 3) Funding cash flow have a positive and not significant on effect stock return, 4) Accounting profit has a negative and no significant on effect return stock, 5) The size of the company has a positive and significant effect on stock return. The limitations of this study were that the adjusted R2 examined only had an effect of 13.2%. This shows that the influence of operating cash flows, investment cash flows, funding cash flows, accounting profit and company size on stock return is still very small compared to other factor, which is 86.8% and influenced by other factors which can be examined further. Future research needs to pay attention to other factors such as grofit, ROA and ROE.Keyword : operating cash flow, investment cash flow, funding cash flow, accounting profit, company size, and stock return.